Study of the Variety of Local Snacks and Pastries in Medan City: Uniqueness, Preferences, and Culinary Culture - Indra, Febryola; Sitorus, Nova Bernedeta; Maleachi, Sandra; Pramono, Rudy; Valensky, Sherla (Jurnal Manajemen Pelayanan Hotel, 2024)
The study titled "Study of the Variety of Local Snacks and Pastries in Medan City: Uniqueness, Preferences, and Culinary Culture" explores the rich diversity of Medan's local snacks and pastries, highlighting their historical roots, cultural significance, and evolving culinary trends. Key findings reveal that traditional snacks like Bika Ambon, Bolu Meranti, Martabak Har, and Getuk Banana each carry unique histories and traditional recipes, reflecting Medan's culinary heritage. Modern pastry trends, incorporating Western influences with local flavors, showcase the dynamic interplay between tradition and innovation. Preferences for these snacks and pastries are influenced by both rational factors, such as price and quality, and emotional and cultural factors, including family habits and childhood memories. The study underscores the multifaceted nature of food preferences and the importance of respecting local culinary traditions while embracing global influences. This comprehensive understanding of Medan's culinary landscape not only celebrates its ethnic diversity and historical richness but also serves as a foundation for sustainable culinary tourism development. By promoting and preserving traditional snacks alongside modern pastries, Medan can attract tourists, strengthen its regional culinary identity, and empower the local economy. Data collection methods include participant observation and in-depth interviews with business owners, sellers, and consumers, providing valuable insights into the role of culinary delights in Medan's culture.